2016
DOI: 10.3847/0004-637x/832/1/50
|View full text |Cite
|
Sign up to set email alerts
|

Banyan. Viii. New Low-Mass Stars and Brown Dwarfs With Candidate Circumstellar Disks

Abstract: We present the results of a search for new circumstellar disks around low-mass stars and brown dwarfs with spectral types >K5 that are confirmed or candidate members of nearby young moving groups. Our search input sample was drawn from the BANYAN surveys of Malo et al. and Gagné et al. Two-Micron All-Sky Survey and Wide-field Infrared Survey Explorer data were used to detect near-to mid-infrared excesses that would reveal the presence of circumstellar disks. A total of 13 targets with convincing excesses were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 111 publications
(136 reference statements)
2
44
0
Order By: Relevance
“…In low-mass stars (0.1-1  M ), the transition from primordial disks to debris disks occur at about 10 Myr, and debris disks peak at the age of 10-30 Myr. In contrast, brown dwarf disks are still in the primordial stage at 10 Myr, and their debris disks seem to largely disappear by the age of 40-50 Myr (Riaz & Kennedy 2014), with rare exceptions (Boucher et al 2016). Thus, it is possible that LSR J1835 still has a disk.…”
Section: Discussionmentioning
confidence: 99%
“…In low-mass stars (0.1-1  M ), the transition from primordial disks to debris disks occur at about 10 Myr, and debris disks peak at the age of 10-30 Myr. In contrast, brown dwarf disks are still in the primordial stage at 10 Myr, and their debris disks seem to largely disappear by the age of 40-50 Myr (Riaz & Kennedy 2014), with rare exceptions (Boucher et al 2016). Thus, it is possible that LSR J1835 still has a disk.…”
Section: Discussionmentioning
confidence: 99%
“…Within the uncertainties, the measured radial velocities are consistent with membership in their assigned moving groups. Figure 3 depicts the spectra for our four targets around the lithium feature at 6707.8Å, along with the spectrum of J0501 (adopted from Boucher et al 2016), degraded to the resolution and rebinned to the dispersion of our data. As seen in Figure 3, we do not detect clear evidence of lithium in our data, deriving upper limits of 0.11-0.25Å.…”
Section: Age Estimates and Radial Velocity Measurementsmentioning
confidence: 99%
“…Additionally, both J0808 and J0501, another Peter Pan disk candidate in the Columba system (Boucher et al 2016), were observed at two-minute cadence from 2018 October 18-November 15 by the Transiting Exoplanet Survey Satellite (TESS; Ricker et al 2014) during Cycle 1, Sector 4, as part of TESS GI Program G011148 (PI Kuchner). J0808 appeared in CCD 4 of Camera 4, while J0501 appeared in CCD 4 of Camera 3.…”
Section: High-cadence Optical Imagingmentioning
confidence: 99%
“…Its W 1 − W 4 color (0.93±0.23) is not red enough to respect the W 1−W 4 > 1.0 criterion of Schneider et al (2012b) for infrared excess (see also Schneider et al 2012a), and a comparison with predictions from BT-Settl models places the infrared excess of this source at a significance below 3σ in these two photometric bands (see Boucher et al 2016). …”
Section: Mass J11112820-2655027mentioning
confidence: 99%